Segodnia v mire . Segodnia v mire . The World Today . Сегодня в мире - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Attack on an American oil tanker; appointment of a new chief executive at the Pentagon; discussion on removing U.S. military bases from other countries. Contributors: Korzin, Valerii (Anchor) Series description: An information program of the Central Television of the USSR (CT USSR). The hosts were Igor Fesunenko, Valentin Zorin, Farid Seiful-Muliukov, and others. The program was first broadcasted on December 1, 1978 and was broadcasted until 1988. Нападение на американский танкер, назначение нового шефа Пентагона, обсуждение вывода американских баз с территории других стран. Создатели: Корзин, Валерий (Ведущий/Ведущая) Описание серии: Информационная телепередача Центрального телевидения СССР. Ведущие — Игорь Фесуненко, Валентин Зорин, Фарид Сейфуль-Мулюков и другие. Первый выпуск передачи вышел в эфир 1 декабря 1978 года. Выходила до 1988 года